Prospects for deploying microbes against tree-killing beetles (Coleoptera) in Anthropocene - Gupta, Sumanti; Chakraborty, Amrita; Roy, Amit (Frontiers in Forests and Global Change, 2023)
Forests form rich biodiversity hubs that act as large reservoirs of natural carbon. The spatial and temporal heterogeneity of these complex habitats of forest floors provides ecological services of immense socio-economic importance. However, these socio-economic ecological hotspots are incessantly exposed to multifarious abiotic, biotic, and anthropogenic disturbances, amongst which unpredictable forest pest (i.e., bark beetle) outbreak account for the loss of vegetation and microbiome of measurable quantum. The importance of the microbiome in forming an inseparable functional unit of every host and shaping its interaction with other partners has been well realized. Interestingly, forest pests, including bark beetles, are also reported to rely on their endosymbiotic microbial partners to manipulate tree defense machinery. In contrast, the microbiome forming the holobiont of trees also regulates the overall function and fitness of the host and significantly contributes to tackling these challenging situations. Nevertheless, how the holobiont of trees directly or indirectly influence beetle holobiont is still an enigma. The present review shall elaborate on the role of microbial tools in enhancing tree performance and fitness, which helps counter beetle damage. Besides, it shall also emphasize exploiting the role of microorganisms in acting as biocontrol agents in shielding the trees against beetle destruction. The application of endosymbiont-mediated RNA interference (RNAi) in working with two-tier specificity for controlling beetle devastations shall be discussed as new-age technological advances. All explanations are expected to put forth the potential of the microbial toolbox in offering better and more sustainable beetle management strategies in the future.